Use of High-Flow Nasal Cannula Oxygen Therapy in Subjects With ARDS: A 1-Year Observational Study - Messika, Jonathan; Ben Ahmed, Karim; Gaudry, Stéphane; Miguel-Montanes, Romain; Rafat, Cédric; Sztrymf, Benjamin; Dreyfuss, Didier; Ricard, Jean-Damien (Respiratory care, 2015)
Beneficial effects of high-flow nasal cannula (HFNC) oxygen on oxygenation and respiratory parameters have been reported in a small number of subjects with acute respiratory failure (ARF). We aimed to evaluate its effect in subjects with ARDS. This was an observational single-center study. Prospectively obtained data were retrospectively analyzed. All patients admitted over 1 y to a university hospital medicosurgical ICU were included. Classification was according to the highest ventilatory support required. HFNC indications were reviewed, and demographics, clinical characteristics, and course of subjects with ARDS according to intubation need were compared. Of 607 subjects admitted, 560 required ventilatory or oxygen support, among whom 180 received noninvasive ventilatory support. HFNC was used in 87 subjects and as first-line treatment in 51 subjects (29% of first-line noninvasively treated subjects), 45 of which had ARDS (PaO2 /FIO2 of 137 mm Hg; 22 men, 57.9 y of age). Pneumonia accounted for 82% of ARDS causes. The intubation rate in these subjects was 40%. Higher Simplified Acute Physiology Score II (SAPS II; 46 vs 29, P=.001), occurrence of additional organ failure (76% vs 26%, P=.002), mainly hemodynamic (50% vs 7%, P=.001) or neurological (22% vs 0, P=.01), and trends toward lower PaO2 /FIO2 and higher breathing frequency after HFNC initiation were evidenced in subjects who failed HFNC. Higher SAPS II scores were associated with HFNC failure in multivariate analysis. In daily care, over one fourth of subjects requiring noninvasive ventilatory support were treated via HFNC, with a high success rate in subjects with severe ARDS. We conclude that HFNC may be considered as first-line therapy in ARF, including patients with ARDS.